2013
DOI: 10.1099/ijs.0.049841-0
|View full text |Cite
|
Sign up to set email alerts
|

Loktanella sediminilitoris sp. nov., isolated from tidal flat sediment

Abstract: A Gram-stain-negative, non-motile, rod-shaped bacterial strain, designated D1-W3 T , was isolated from tidal flat sediment of the South Sea, South Korea, and subjected to a taxonomic study using a polyphasic approach. Strain D1-W3 T grew optimally at pH 7.0-8.0, at 25 6C and in the presence of 2 % (w/v) NaCl. Neighbour-joining phylogenetic analyses based on 16S rRNA gene sequences revealed that strain D1-W3 T fell within the clade comprising species of the genus Loktanella, clustering with the type strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…The polar profile of L. sediminilitoris KCTC 32383 T differed from those of the other four strains studied in that phosphatidylethanolamine (PE) was detected. This finding is congruent with the original description by Park et al (2013a) who reported the presence of PC, PG, PE and an unknown aminolipid as dominant and DPG, an unknown phospholipid and an unknown lipid as minor components in L. sediminilitoris KCTC 32383 T . In addition, unknown phospholipids PL1-PL3 were found in the present study.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The polar profile of L. sediminilitoris KCTC 32383 T differed from those of the other four strains studied in that phosphatidylethanolamine (PE) was detected. This finding is congruent with the original description by Park et al (2013a) who reported the presence of PC, PG, PE and an unknown aminolipid as dominant and DPG, an unknown phospholipid and an unknown lipid as minor components in L. sediminilitoris KCTC 32383 T . In addition, unknown phospholipids PL1-PL3 were found in the present study.…”
supporting
confidence: 82%
“…DResults differ from those reported by Park et al (2013a). dData not consistent with those reported by Yoon et al (2007).…”
Section: Ketogulonicigenium Vulgare Dsm 4025 T (Af136849)contrasting
confidence: 56%
See 2 more Smart Citations
“…Subsequently, the names Loktanella hongkongensis (Lau et al, 2004), Loktanella agnita and Loktanella rosea (Ivanova et al, 2005), Loktanella koreensis (Weon et al, 2006), Loktanella atrilutea (Hosoya & Yokota, 2007), Loktanella maricola (Yoon et al, 2007), Loktanella pyoseonensis (Moon et al, 2010), Loktanella tamlensis (Lee, 2012), Loktanella cinnabarina (Tsubouchi et al, 2013), Loktanella litorea , Loktanella sediminilitoris (Park et al, 2013), Loktanella maritima (Tanaka et al, 2014), Loktanella ponticola (Jung et al, 2014), Loktanella soesokkakensis (Park et al, 2014a), Loktanella variabilis (Park et al, 2014b) and Loktanella sediminum (Liang et al, 2015) have been validly published. In this study, we describe a bacterial strain, designated MDM-7 T , which was isolated from seawater collected at Taean of the Yellow Sea in South Korea.…”
mentioning
confidence: 99%